Is viscoelasticity of any relevance to quantitative EHL friction predictions? - Habchi, Wassim (2019)
The classical study of friction in elastohydrodynamic lubrication (EHL) has often invoked viscoelastic response to explain the friction behavior at small slide-to-roll ratios. In these studies the shear modulus has been, like viscosity, an adjustable parameter, used to reconcile theory with experiment. The very low values of shear modulus employed should have required the use of an objective form of the time derivative. Here, the known properties, including shear modulus, are applied to a full line contact simulation to settle, once and for all, the relevance of viscoelasticity to EHL friction. It is shown that the influence of shear viscoelasticity on EHL friction is negligible in comparison with the roller elastic creep which must be included in a prediction.